Influence of covid-19 and other respiratory diseases in the gestational period (Research, Society and Development, 2020)
This research aimed to describe the main risks of being affected by covid-19 and other respiratory diseases during pregnancy. The present study is an exploratory research, of the literature review type. The searches were carried out between January 2020 and March 2020, using the Scielo, Science Direct, Google scholar and PubMed databases, with the time frame from 2016 to 2020. There was a careful selection with respect to the works used for the development of this review. The descriptors used, in an associated and isolated way, were: “COVID-19”, “PREGNANT”, “RESPIRATORY DISEASE”, “RISK” AND “TREATMENT”, in English, Spanish and Portuguese and indexed in the DECs. At the end of the analysis, 10 articles were selected. It is concluded that, possibly, the pathogenic potential of COVID-19 is similar to that of SARS-CoV and MERS-CoV, so that the virus would be capable of causing serious maternal or perinatal results. It is recommended to carefully evaluate any febrile respiratory disease in pregnancy, carrying out appropriate diagnostic investigations.